Identification of Samin Community Culture in Bojonegoro Towards Environmental Sustainability in Rural Area - Alfian, Rizki; Setyabudi, Irawan; Santoso, Dian Kartika (Journal of Civil Engineering, Planning and Design, 2022)
Globally, currently more than 50 percent of the world's population lives in urban areas. It is projected that 70 percent of the world's population will live in cities by 2050. Given the sheer scale of urbanization and its environmental implications, it is important to consider the interrelationships between urban and rural contexts in an integrated manner. Achieving sustainable development requires priorities and the implementation of tailored policies in both urban and rural areas. One way that can be done is to strengthen rural cultural values in communities and indigenous peoples. In this study, the case study raised is the cultural value of the Samin Bojonegoro community in maintaining cultural values and preventing the flow of urbanization of its population. The creation of a livable environment through the cultural values of the Samin community will be raised through this research through ethnographic approach with synchronic and diachronic presentation. As a result The Samin community, which is rooted in the culture of an agrarian society, has not changed much in terms of vegetation, land use, and cultural activities. This has an impact on environmental sustainability and cultural establishment so that it seems as if it has a border from outside influences while also protecting cities from urbanization flows and environmental burdens